PEMBUATAN KOMPOS BERBAHAN BAKU LIMBAH LUMPUR PABRIK KERTAS DENGAN PENAMBAHAN TRICHODERMA HARZIANUM - FITRI, INAYAH (Universitas Negeri Surabaya, 2013)
Sludge in the paper mill is now large. Utilization of sludge as composting is one alternative to use it. But the problems and constraints faced is the composting process takes about 3 months. In order to speed up the composting process, the addition of fungus T. harzianum is one of the alternative. The purpose of this study was to describe the quality of the nutrient concertation of sewage sludge compost from paper mill with the addition of T. harzianum as N, P, K, and C/N ratio. Descriptive data were analyzed by comparing the nutrient content and the soil criteria based on Hardjowigeno. The results showed that the addition of T. harzianum affected the quality of the nutrient of N, P, K and C/N ratio in compost. The concentration of N, P, K, and C/N ratio were 1.09% (very high), 0.24% (medium), 0.28 % (low) and 17 (high).